(untitled) (Journal of Applied Juvenile Justice Services, 2021)
In 2008, Luzerne County, Pennsylvania made national headlines when the “Kids for Cash Scandal” broke. As a result of the actions of the Juvenile Court Judge and other juvenile system personnel, the Interbranch Commission on Juvenile Justice was created to develop rules to prevent the juvenile justice system in Pennsylvania from failing again. The purpose of this study was to determine how juvenile probation practices have changed since the scandal and if those departments were following through with the recommendations of the Commission. While many policies and practices have changed since the scandal, such as the policies regarding gifts and gratuities, there was a lack of consistency in the magnitude of those changes.